Psychological approach to some sensory perceptions in mentally retarded children - Khosilova Ziyofat Beg murotovna; Sobirova Mohinur Bahrom kizi (THE INNOVATION ECONOMY, 2026)
The process of forming the relationship between objects and phenomena as a whole or their various prop erties, which directly affects the human sensory analyzers or system of analyzers, is called perception. Perception is formed on the basis of various sensations. In psychology, this concept is studied by distinguishing the following 5 types: vision, hearing, tactile (skin sensation), taste and smell. The objective activity of perception is the development of human activity. At the same time, activity, practice contribute to the development of perception, the full and cor rect reflection of actions. Mentally retarded children are characterized by late and incomplete formation of all types of activity. This depends on the development of thinking and speech at a certain level, abilities, attention and the ability to direct their volitional actions towards a goal